Peran Ekonomi Syariah Dan Ekonomi Kreatif Sebagai Sumber Pertumbuhan Ekonomi - Harahap, Sunarji (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2024)
Bank Indonesia continues to strive to improve the performance of the Islamic economy which continues to grow in Indonesia, this is reflected in the increasing Indonesia's ranking at the global level based on the State of the Global Islamic Economy (SGIE) Report, from fourth place in 2023 to third place in 2024, with the strongest components in halal food and beverage and Muslim-friendly tourism (PRM). From the financial side, the role of Islamic banking in economic financing also continues to increase. Islamic banking financing to the real sector experienced a growth of 15.8%, higher than the overall real sector financing which grew by 10.5%. The halal food and beverage sector in 2023 grew strongly to reach 4.47% (yoy). This is due to public demand and halal food and beverage exports which are still quite strong, supported by strong public demand and still strong halal food and beverage exports.